Ecophysiological and agronomic responses of perennial grass species under water stress - Beloni, Tatiane (2015)
The total annual forage production of tropical grasslands in the Brazilian Central area is expected to increase, however, some studies also predict a higher variability of forage production between and within years. In the future, maintenance of many pastures áreas will probably depend on the use of technology and increased productivity, seeking a competitive advantage concerning other activities, or even on its relocation to marginal áreas where forage grasses will be more suitable to abiotic factors. The water stress, both by flooding and drought, may reduce the production and survival of grasses. The objective was to identify the strategies that some genotypes of Paspalum and Urochloa genus use to cope with the flooding and/or water deficiency in the soil. Two greenhouse experiments were conducted: 1 - morphological and physiological characteristics, survival rate and recovery index in five genotypes of Paspalum sp. (BRS Guará, BGP 289, BGP 293, BGP 402 and BGP 397) and U. brizantha cv. Marandu were evaluated under three water conditions (flooded, drought and control); 2 - dehydration tolerance and dehydration avoidance of three cultivars of Urochoa (\'Marandu\', \'BRS Paiaguás\' and \'Basilisk\') and a cultivar Mediterranean Dactylis glomerata L. cv. Medly. In experiment 1, the genotypes of Paspalum sp., especially BGP 289, BGP 402, BGP 397 and cv. Marandu previously submitted water déficit, presented high tiller survival rates after rehydration. The cv. Marandu and BGP 289 access were not tolerant to flooding, presenting a low tiller survival rate and root recovery index. The BGP 293 access was not resistant to flooding, but it was able to survive periods up to 28 days under water depth. The accesses of Paspalum BRS Guará, BGP 402 and BGP 397 presented resistance mechanisms and survival to flooding, related to a high concentration of chlorophyll in the leaf, leaf biomass, and root recovery and tiller survival after a recovery period under water regular condition. In experiment 2, the distinction of cultivars was in accordance with the resource-use strategy. Cultivars of Urochloa were less tolerant to dehydration than cv. Medly. But the most productive Urochloa cultivars (Marandu and Basilisk) further delayed dehydration due to high investment in the root system, and consequently were less dehydration tolerant, with less survival rates under severe drought. The cv. BRS Paiaguás was less productive under regular irrigation than other Urochloa cultivars, but under drought conditions it is closer to the cv. Medly, being highly dehydration tolerant, and presenting high survival rates under severe drought and dehydration avoidance strategies with roots elongation along the soil profile during the drought period. There are differences in responses to other deficit and flooding between and within the Paspalum and Urochloa genus morphophysiological traits used in this study are relevant for the understanding of the mechanisms and discrimination among genotypes.